ANALISIS SPASIAL HUBUNGAN KUALITAS LINGKUNGAN DENGAN KEJADIAN DIARE PADA BALITA DI KECAMATAN GENUK KOTA SEMARANG - Mawaddah Muhajjar; Mursid Rahardjo; Nikie Astorina Yunita Dewanti (Jurnal Kesehatan Masyarakat (Undip), 2016)
Diarrhea  is still being one of health problem in Indonesian society. Based on Bangetayu Puskesmas and Genuk Puskesmas in 2015 show that the cases of  diarrhea on childrenunder five years increases  from the previous year. Environmental conditions in some areas of  Genuk  District that are experiencing floods can also causes diarrhea disease. The purpose of this study is to analyze the spatial relationship of environmental quality with the cases of diarrhea on children under five years in Genuk District, Semarang. Research method of this research applies observational analytic design by using a cross sectional study design.The location is in Genuk district, Semarang. The number of population of this research is 12.443 children under five years in 2015. The writer employed 43 respondents that are specified  by incidental sampling technique.  The  analysis of the research is conducted by using Chi Square test. The resultsshow 72.1%  incidence of diarrhea. Furthermore 81.4% bacteriological quality of water, 72.1% waste disposal facility conditions, 65.1% sewerage conditions, and 41.9% of clean and healthy behaviors are not eligible. The results of this research show that there are  significant relationship between the conditions of disposal facilities garbage (p = 0.002), the condition of sewerage (p = 0.018), the behavior of healthy and clean living (p = 0.015) toward the incidence of diarrhea on children under five years. There is no relationship significantly between the quality of bacteriological water regarding the incidence of diarrhea on children under five years. Spatial analysis shows that the areas that very susceptible to affect a diarrhea disease caused by bacteriological quality of water, waste disposal facility conditions, the conditions of SPAL which are not complied with the requirement, and lack of clean and healthy behaviors are not eligible. In line with Spatial analysis, Genuksari(16.13%).,Karangroto(16.13%), and Bangetayu Village Wetan (12.90%) villages provide high estimation toward diarrhea disease risks. It is highly recommended that society must attention to the environment as prevention of diarrhea on children under fiver years.